2022
DOI: 10.1155/2022/3523432
|View full text |Cite
|
Sign up to set email alerts
|

Yoga, Meditation, Breathing Exercises, and Inflammatory Biomarkers with Possible Implications in COVID-19: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Introduction. COVID-19, a multisystem disease, has implications for various immunity and infection biomarkers. Yoga (Y), meditation (M), and pranayama (P), and their combinations have shown positive changes on those biomarkers among other than COVID-19 patients and healthy people. So, we aimed to document the evidence of possible implication in a systematic way. Materials and Methods. We screened 84 full texts, published in the last ten years, from three databases, from which only 44 met the eligibility criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Children and adolescents with COVID-19 have a worse HRQoL (Shah et al, 2022). According to the findings, those suffering with Post COVID-19 Syndrome(PCS) have a worse quality of life and have chronic symptoms such as tiredness, dyspnea, anosmia, sleep problems, and impaired mental health.…”
Section: Quality Of Life (Qol) In Covid-19mentioning
confidence: 99%
“…Children and adolescents with COVID-19 have a worse HRQoL (Shah et al, 2022). According to the findings, those suffering with Post COVID-19 Syndrome(PCS) have a worse quality of life and have chronic symptoms such as tiredness, dyspnea, anosmia, sleep problems, and impaired mental health.…”
Section: Quality Of Life (Qol) In Covid-19mentioning
confidence: 99%
“…Better sleep quality and lower cortisol levels were reported following yoga as compared to cognitive behavior therapy. Both the decreased cortisol levels and enhanced sleep quality following yoga versus cognitive behavior therapy likely derived from increased parasympathetic activity following the stimulation of pressure receptors during yoga [59].…”
Section: Potential Underlying Biological Mechanismsmentioning
confidence: 99%
“…The Ayurvedic system of medicine employs a variety of modalities, including manual therapies, nutritional therapy, herbal remedies, lifestyle counseling, and yoga exercises based on yoga [17]. Various studies (case reports, randomized controlled trials (RCTs), and meta-analyses) have demonstrated Ayurveda's efficacy and safety as a treatment for various ailments, both communicable and non-communicable [18][19][20]. It has been demonstrated to be a cost-effective alternative for boosting immunity, with few hazardous side effects and ease of use [21].…”
Section: Introductionmentioning
confidence: 99%